Feasibility of measuring arsenic and selenium in human skin using in vivo x-ray fluorescence (XRF)—a comparison of methods. (18th December 2015) - Shehab, H; Desouza, E D; O'Meara, J; Pejović-Milić, A; Chettle, D R; Fleming, D E B; McNeill, F E
Abstract: In recent years, in vivo measurement systems of arsenic in skin by K-shell x-ray fluorescence (XRF) have been developed, including one which was applied in a pilot study of human subjects. Improved tube-based approaches suggest the method can be further exploited for in vivo studies. Recently, it has been suggested that selenium deficiency is correlated with arsenic toxicity. A non-invasive measurement of both elements could therefore be of potential interest. The main aim of this current study was to evaluate and compare the performance of an upgraded portable XRF system and an advanced version of the benchtop XRF system for both selenium and arsenic. This evaluation was performed in terms of arsenic and selenium K α detection limits for a 4W gold anode Olympus InnovX Delta portable analyzer (40 kVp) in polyester resin skin-mimicking phantoms. Unlike the polychromatic source earlier reported in the literature, the benchtop tube-based technique involves monochromatic excitation (25 W silver anode, manufactured by x-ray optics, XOS) and a higher throughput detector type. Use of a single exciting energy allows for a lower in vivo dose delivered and superior signal-noise ratio. For the portable XRF method, arsenic and selenium minimum detection limits (MDLs) of 0.59 ± 0.03 ppm and 0.75 ± 0.02 ppm respectively were found for 1 min measurement times. The MDLs for arsenic and selenium using the benchtop system were found to be 0.35 ± 0.01 ppm and 0.670 ± 0.004 ppm respectively for 30 min measurement times. In terms of a figure of merit (FOM), allowing for dose as well as MDL, the benchtop system was found to be superior for arsenic and the two systems were equivalent, within error, for selenium. We shall discuss the performance and possible improvements of each system, their ease of use and potential for field application.